Impact of Glucose Addition on The Embryo Development of Climbing Perch (Anabas testudineus Bloch) - Fauzi, Akhmad; Slamat, Slamat; Rukmini, Rukmini (Universitas Islam Lamongan, 2025)
The addition of glucose to the hatching medium is thought to enhance the embryonic development of climbing perch by providing additional energy, strengthening metabolic stability. This research aims to analyze the impact of glucose addition on the embryonic development of climbing perch in developing efficient, sustainable, and conservation-oriented hatchery technology. The study was conducted in the Ulin River, North Banjar Baru District, with broodstock climbing perch from BBII Karang Intan, aged less than 1.5 years and weighing at least 100 g for females and 50 g for males. Fertilized eggs were then incubated in aquadest incubation media using 20 petri dishes, and the media was given glucose solution according to the treatment, namely 0.2 g/100 mL (A), 0.4 g/100 mL (B), 0.6 g/100 mL (C), and without the addition of glucose as a control (D). The addition of glucose solution to the hatching medium has a positive effect on embryo development. Glucose helps increase the metabolic activity of the embryo, accelerates development, and produces optimal hatching power (100%).